PEMBINAAN PUSDIKLAT TENIS LAPANGAN SEMEN GRESIK - NINO, ASA (Jurnal Prestasi Olahraga, 2013)
Tennis can be considered as a kind of sport aimed for either achievement or leisure, depending on its purpose of play. For leisure, tennis is played to improve your fitness and get rid of dullness. For achievement, tennis can be used as a job to earn a living. However, to have such achievement, it needs lots of supporting factors such as athlete, coach, organization, infrastructure, surrounding environment and government. All factors are linked to each other to have such a good achievement. Pusdiklat or training center is a place functioned to learn or exercise in order to teach and develop potency possessed by athlete to reach certain goals or accomplishments. Semen Gresik is a company owned by government, which facilitates a training center to follow up a proposal of PELTI focusing on improving accomplishments of tennis in Indonesia, and East Java in particular. This research is aimed to identify and describe development of training center of Semen Gresik in terms of profile, management, education and some other factors. It is a qualitative research using descriptive method. Data were taken in the company area of Semen Gresik, which has tennis training center of Semen Gresik. Research subjects are chief of training center, coach, athlete and staffs. Data were taken and processed using data analysis through interviewing research subjects, namely, chief, coach, athlete, staffs of training center of Semen Gresik. From this research, it can be concluded that tennis training center of Semen Gresik has run good management supported by organized training course, licensed coach, proper facilities and infrastructure. These conditions result in a series of accomplishments that athlete can be proud of. However, there are only a few coach assistant and lack of discipline of athlete that can be considered as hindering factors. Key Words: Academy, Management, Tennis